Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T20:58:56+01:00
A1 + a2 + a3 + a4 + a5 = 93
a3 + a4 +a5 +a6 + a7 = 372
Odejmujemy stronami
a7 + a6 - a2 - a1 = 372 - 93 = 279
a1*q⁶ + a1*q⁵ - a1*q - a1 = 279
a1*(q⁶ + q⁵ -q -1) = 3*93
a1 = 3
q⁶ + q⁵ - q -1 = 93
q*(q⁵ + q⁴ -1) = 93 + 1 = 94 = 2*47
q = 2
sprawdzam czy
q⁵ + q⁴ - 1 = 47
2⁵ + 2⁴ - 1 = 32 + 16 - 1 = 48 - 1 = 47
Należy jeszcze sprawdzić czy spełnione są dwa początkowe
równania. Okazuje sie, ze tak , bo
3 +6 + 12 + 24 + 48 = 93
oraz
12 + 24 + 48 + 96 + 192 = 372
Odp.a1 = 3 oraz q = 2
9 2 9